Treatment of Household Grey Water Using a Series Anaerobic Biofilter - Wetland - Arlini Dyah Radityaningrum; Maritha Nilam Kusuma (Future Science)
The study aimed to treat household grey water, focusing on technology that is simple and low cost in terms of operation and maintenance. The treatment was conducted within laboratory scale based using a series continuous reactor of anaerobic biofilter and wetland. The anaerobic biofilter was equipped with plastic derived from Poly Ethylene Terephthalate (PET) as biofilter media. Subsequent wetland used vertical sub-surface flow constructed wetland (VSSF CW). Removal efficiency of TSS, BOD, COD achieved from anaerobic biofilter was 84%, 79%, 57% respectively, while wetland resulted TSS, BOD, COD removal of 81%, 84% and 67% respectively.